Development of Augmented Reality-Based Digital Literacy Media to Improve Elementary School Students' Understanding of Cultural Diversity - Mazidah, Ismi; Rosidah, Cholifah Tur; Rachmadtullah, Reza (Journal La Edusci, 2025)
This research aimed to develop digital literacy media based on Augmented Reality (AR) to enhance elementary school students' understanding of cultural diversity. The research used the Instructional Development Institute (IDI) model, consisting of three main stages: define, develop, and evaluate. In the defined stage, the researchers conducted a needs analysis through curriculum review and classroom observation. During the development stage, AR-based media containing 3D representations of local Indonesian cultures such as traditional houses, dances, and attire was designed and validated by subject matter and media experts. In the evaluate stage, the media was tested through limited and wider trials using a pretest–posttest design. Data were collected through observation, questionnaires, interviews, and tests. The results showed that the developed media was valid, practical, and effective in improving students’ cultural understanding. The study concluded that the integration of AR in digital literacy media provided an immersive and meaningful learning experience that supports 21st-century skills and character education aligned with the Merdeka Belajar curriculum.